Identitication offastigioblabar pathways by horseradish peroxidase method - Abdulcholiq Chuseri Abdulcholiq Chuseri (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
In this experiment the fastigial projection to the paramedian reticular nucleus was investigated by means of retrograd axonal transport of horseradish peroxidase (HRP) in the rabbit cerebellum. Following HRP injection in various regions of the paramedian reticular nucleus of the medulla oblongata, labelled cells were found in the fastigial nucleus on both sides with a greater preponderance on the contralaterai side. Most of the labelled cells were distributed in the rostra] and medial regions of the fastigial nucleus, after HRP injection in the area of the paramedian reticular nucleus, proved that the fastigial neurons project their axons to the paramedian reticular nucleus.Key Words: fastigiobulbar pathways - horseradish peroxidase - fastigial nucleus - paramedian reticular nucleus - medulla oblongata